2018
DOI: 10.35188/unu-wider/2018/507-7
|View full text |Cite
|
Sign up to set email alerts
|

Early life shocks and mental health: The long-term effect of war in Vietnam

Abstract: This study has been prepared within the UNU-WIDER project on 'Structural transformation and inclusive growth in Viet Nam'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
4
7
0
Order By: Relevance
“…Our results combined with a review of the theory and historical literature suggest that the likely pathway is through direct exposure to the bombing and other correlated ordnance and weapons including UXO, landmines, and dioxin, as well as through indirect mechanisms relating to poor nutritional environment, human capital depletion, and low quality public healthcare. Taken together with the earlier work of Miguel & Roland (2011) and Singhal (2018), our findings suggest that wars inflict costs on the health of human populations that last longer than those relating to economic growth and welfare. These findings from Vietnam underpin the importance of expediting the process of cleaning up the consequences of war, and in ensuring food security and adequate health and rehabilitation services for people in conflict-affected zones.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our results combined with a review of the theory and historical literature suggest that the likely pathway is through direct exposure to the bombing and other correlated ordnance and weapons including UXO, landmines, and dioxin, as well as through indirect mechanisms relating to poor nutritional environment, human capital depletion, and low quality public healthcare. Taken together with the earlier work of Miguel & Roland (2011) and Singhal (2018), our findings suggest that wars inflict costs on the health of human populations that last longer than those relating to economic growth and welfare. These findings from Vietnam underpin the importance of expediting the process of cleaning up the consequences of war, and in ensuring food security and adequate health and rehabilitation services for people in conflict-affected zones.…”
Section: Discussionsupporting
confidence: 78%
“…Exposure to armed conflict in utero or in early childhood or adolescent years is associated with substantially lower height or height-for-age scores (a proxy for long-run nutritional status and health) in later life in multiple contexts (Akresh, Lucchetti & Thirumurthy, 2012; Bundervoet, Verwimp & Akresh, 2009; Grimard & Laszlo, 2014; Minoiu & Shemyakina, 2014). Exposure to armed conflict in childhood has also been linked to long-lasting detrimental effects on mental health, self-rated health satisfaction, BMI, and chronic health conditions such as stroke, hypertension, diabetes, and cardiovascular disease (Akbulut-Yuksel, 2014, 2017; Singhal, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Armed conflict deteriorates both physical capital and human capital, which hinders a nation's future development. Studies of armed conflict have found that early‐life health plays a critical role in socioeconomic outcomes because children exposed to armed conflict in utero are likely to be less educated (see Ouili, 2017 for Cote d'Ivoire; Weldeegzie, 2017 for Ethiopia), less healthy in adulthood (see Akresh, Bhalotra, Leone, & Osili, 2012 for Nigeria; Akbulut‐Yuksel, 2017 for Germany; Singhal, 2018 for Vietnam) and in early childhood (see Akresh, Lucchetti, & Thirumurthy, 2012 for Eritrea; Akresh, Caruso, & Thirumurthy, 2014 for Ethiopia and Eritrea; Bundervoet, Verwimp, & Akresh, 2009 for Burundi; Guantai & Kijima, 2020 for Kenya; Minoiu & Shemyakina, 2014 for Cote d'Ivoire; Shemyakina, 2018 for Zimbabwe; Tranchant, Justino, & Müller, 2014 for India), and less likely to survive in utero and during the first year of life (see Dagnelie, Luca, & Maystadt, 2018 for Democratic Republic of Congo; Wagner et al, 2018 for Africa). Although studies examining the effect of armed conflict in SSA have recently been growing, there are some methodological challenges to identifying those actually exposed to conflict.…”
Section: Introductionmentioning
confidence: 99%